Románia, mint befektetési célterület - Juhász, Krisztina (Közép-Európai Közlemények, 2012)
Romania became in the last years one of the emerging markets in Central and Eastern Europe. Due to some positive processes (privatization, join to the EU, investment politics) increased the foreign direct investments to Romania in a very fast way. The FDI inward stock of Romania reached in 2010 more than 70 billion USD, what was 10 times higher than 10 years before. Regarding the FDI inflow trends, Romania became the third most important host country in Central and Eastern Europe during the last few years. Romania is also an important host country for the Hungarian companies investing abroad. There are 10.000 companies with Hungarian share in Romania. Some of the biggest investors are MOL, OTP, RG, Fornetti, Dunapack, Pipelife Romania, Salina Invest and Lasselsberger. The motivation of these Hungarian companies are quite complex. We can find market and resource seeking investments as well. The most important competitive advantages of Romania are the market (mainly the market size) and the labour (manily the price, the efficiency and the readness of technology). On the other hand, the quality of infrastructue, the government institutions (the favoritism of government officials decisions, wastefullnes of government spending, transparency of policy making) and the quality of the labour market (R&D, quality of education) means disadvantages, which can be an obstacle to the increase of the country’s competitiveness. Without all these factors it is hard to imagine how could Romania reach the innovation driven phase of the development.